The Mediating Role of Cognitive Flexibility in the Relationship Between Islamic Religiosity and Moral Intelligence - Mohamed Ali Nemt-allah; Abdulhamid Fathi Alholah; Ahmad Muhammad Ibrahim; Abdalla Elsayed Ibrahim; Nahed Khaled Ayoub; Ashraf Ragab Ibrahim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Grounded in the theoretical premise that Islamic religiosity constitutes a comprehensive ethical framework that may foster cognitive adaptability, which in turn supports moral reasoning, this study investigated the mediating role of cognitive flexibility in the relationship between Islamic religiosity and moral intelligence among Muslim university students. Using a cross-sectional correlational design, data were collected from 637 students (115 males, 522 females) aged 18-23 years at Al-Azhar University in Egypt. Participants completed validated measures assessing Islamic religiosity (beliefs and commitment/practice), cognitive flexibility, and moral intelligence (responsibility, honesty, forgiveness, conscience, and compassion). Structural equation modeling revealed that Islamic religiosity positively correlated with both cognitive flexibility (β = .27, p < .001) and moral intelligence (β = .39, p < .001). Mediation analysis using Hayes's PROCESS macro with 5,000 bootstrap samples demonstrated that cognitive flexibility significantly mediated the religiosity-moral intelligence relationship, accounting for 37.3% of the total effect (indirect effect = .30, 95% CI [.21, .40]). The direct association between Islamic religiosity and moral intelligence remained significant (β = .24, p < .001), indicating partial mediation. Together, Islamic religiosity and cognitive flexibility explained 41.6% of variance in moral intelligence. These findings suggest that religious engagement associates with moral reasoning through dual pathways: directly through religiosity's inherent ethical framework, and indirectly through cognitive adaptability. Results have important implications for Islamic higher education, suggesting interventions might integrate religious instruction with cognitive flexibility training to support students' ethical development.